DESIGN AND IMPLEMENTATION OF SMART FOOD MONITORING SYSTEMS USING IOT AND ELECTRICAL SENSING TECHNOLOGIES (International Journal of Food and Nutritional Sciences, 2022)
Abstract: The integration of Internet of Things (IoT) and electrical sensing technologies in smart food monitoring systems has transformed food safety and quality management. These systems enable continuous, real-time monitoring of critical food parameters such as temperature, humidity, pH levels, and spoilage indicators, ensuring optimal conditions throughout the supply chain. This paper explores the design and implementation of such systems, focusing on sensor selection, IoT integration, and data processing. It details the architecture of smart food monitoring systems, including the role of sensors, communication protocols, data processing units, and user interfaces. The paper also addresses the challenges associated with deploying these systems, such as sensor calibration, data security, scalability, and environmental factors. Solutions to these challenges are proposed to enhance system reliability and effectiveness. Through case studies in cold chain monitoring and food processing quality control, the practical applications and benefits of these systems are demonstrated. The paper concludes by highlighting future directions, including advancements in sensor technology, IoT communication, and data analysis, which promise to further improve food safety and quality management.